Work-life balance, organizational support, and emotional intelligence on banking employee performance through organizational commitment - Janiarti, Della; Shalahuddin, Ahmad; Fauzan, Rizky; Hendri, Muhammad Irfani; Fahruna, Yulyanti (Junal Ilmu Manajemen, 2025)
Banking sector in West Kalimantan is growing, and the majority of the current workforce consists of Generation Y and Z employees. However, the high expectations from organizations to accomplish improved and stable banking performance pose a challenge for these employees. This investigation endeavors to comprehend the variables that affect employee performance, including organizational commitment, work-life balance, organizational support, and emotional intelligence. A sample of 200 respondents was evaluated using questionnaires and Structural Equation Modeling (SEM). The findings indicated that work-life balance, organizational support, emotional intelligence, and organizational commitment impact employee performance. Furthermore, organizational commitment mediated the association between employee performance and the other variables. This research suggests that the banking sector should focus on improving employee productivity by ensuring a good work-life balance, providing effective organizational support systems, and fostering strong organizational commitment.